ANALISIS KESELAMATAN KERJA KARYAWAN PT BUMITAMA GUNAJAYA AGRO, REGION PUNDU KALIMANTAN TENGAH - Puspita, Mita Dwi; Suswatiningsih, Tri Endar; Nurjanah, Danik (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Efforts to maintain work safety are carried out to increase employee productivity and reduce costs due to work accidents. PT Bumitama Gunajaya Agro has implemented an occupational health and safety management system in production activities including harvesting, spraying and fertilizing activities but work accidents are still found in these activities. Therefore it is necessary to identify the hazard, risk assessment and control of the hazard    Abstract. The method used in this research is HIRARC (Hazard Identification, Risk Assessment, Risk Control). From the results of this study the highest source of hazard was found in fruit cutting activities (42.9%), in spraying and fertilizing activities the highest sources of danger were in spray application activities (60%) and fertilizer application (20%). Assessment of the risk of work accidents in harvesting, spraying and fertilizing activities is in the low category. Control is carried out by means of substitution, administration and the use of personal protective equipment.